The Effect of the Implementation of the ICARE Learning Model on the Physics Learning Outcomes of Students of Class XII IPA - Asmara, Anjar; Husna, Husna; Yanti, Iing Rika (Yayasan Pendidikan Bima Berilmu, 2025)
The constructivist approach with educators as facilitators to students is ICARE's learning model because ICARE learning requires students to make introductions, connect new material with previous material, students apply knowledge directly to real problems happening around them, reflect and expand their understanding of the material from educator to student. The purpose of this study is to find out whether there is an influence on students' physics learning outcomes using the ICARE learning model. This study used a quasi-experimental design for 4 meetings. The results of the research obtained in the cognitive realm were in the experimental class (61.63) and the control class (60.35). After the Mann-Whitney test was carried out, an Asym score was obtained. Sig (2-tailed) is 0.573 > 0.05 so, the hypothesis is rejected. Therefore, it can be concluded that there is no significant effect of the application of the ICARE learning model on the learning outcomes of science physics class XII.